Strategi SWOT Untuk Branding Up Setelah Pandemi Terhadap Perusahaan Jasa Perhotelan Di Jakarta Utara - Marlina Marlina (CV. Ulil Albab Corp, 2025)
The COVID-19 pandemic significantly impacted the global economy, including Indonesia’s Hotels industry. For the first time since 2019, Jakarta surpassed Bali in the number of star-rated hotels, with 392 establishments in 2020 compared to Bali's decline. The pandemic caused severe economic setbacks, including 40,000 hotel booking cancellations nationwide, resulting in losses exceeding IDR 1 trillion. This study examines the application of the SWOT strategy in four selected hotels—Hariston Hotel, Aston Pluit, Holiday Inn Express, and Mercure PIK Hotel—to enhance service quality and maintain business sustainability post-pandemic. Data were collected through observations and interviews with hotel employees. The findings reveal that the SWOT strategy plays a pivotal role in boosting occupancy rates and visitor numbers while supporting business continuity. Furthermore, the research highlights the adaptability of the SWOT framework beyond hospitality, underscoring its utility in improving corporate performance, product quality, and human resource competencies. These results emphasize the strategic importance of SWOT analysis in navigating post-pandemic recovery and enhancing organizational resilience.